Experimental Diabetes and Estrogen - Acevedo, Darío (1952)
Diabetes is caused by a disturbance of the endocrine mechanism regulating carbohydrate metabolism. In this regulation, involving the liver, endocrine pancreas, anterior pituitary, adrenal cortex and thyroid.